Men's and Women's Networks: A Study of Interaction Patterns and Influence In an Organization - Brass, Daniel J. (Academy of Management Journal, 1985)
This study investigated the interaction patterns of men and women in an organization and the relationship of these patterns to (1) perceptions of influence, and (2) promotions to supervisory positions. Results indicated that individuals' positions in workflow and interaction networks relate strongly to measures of influence. Although women were rated as less influential than men, the two groups showed no difference on many measures. However, women were not well-integrated into men's networks including the organization's dominant coalition, and vice versa. Women whose immediate workgroups included both men and women were exceptions. A follow-up indicated that promotions were significantly related to centrality in departmental, men's, and dominant-coalition interaction networks.